Art as a Cultural Politics and Diplomacy - Dicky Rezadi Munaf (Institut Seni Indonesia Denpasar, 2016)
As a creative activity, art cannot be merely understood as an individual expression, but a social stage, in which common aesthetic experiences are socially built. Being a social product, art is a medium of various socio-political interests, particularly the interests of a particular community or institution. By employing a participatory research method, this paper is aimed at understanding of how art is used by a particular state’s institution for two interrelated functions. Internally, art is used to create social cohesion and commonality, to enhance work‘s productivity and creativity in the institution. Externally, art is practiced as form of cultural diplomacy, to promote national political, economical and cultural interests in the context of international relation. The conclusion of the research is that the functions of art in the context of state‘s institution are as a form of esthetic experience, institutional and community building, cultural exchange and cultural diplomacy.Keywords: Art, Aesthetic, Institution, Cultural Diplomacy, National Security and Safety.